Correlation between Perfusion-Weighted Magnetic Resonance Imaging (MRI) Features with Histopathological Grading of Glioma (Bangladesh Journal of Neurosurgery, 2023)
Background: Gliomas are the most common primary neoplasm of the brain. It histopathologically grades I to IV. I and II are low grade while III, IV are high grade. Low-grade gliomas are usually subject to either strict follow-up or surgery. The treatment for high grade gliomas is typically surgery, followed by concomitant radiation therapy and chemotherapy. Conventional MRI has limitations for the grading of gliomas. In addition to conventional MRI techniques, a variety of new techniques such as perfusion-weighted MRI which noninvasively measures cerebral perfusion that can be used for better assessment of glioma. This will be helpful for therapeutic approach and counseling about prognosis of the patient.Methods: This cross sectional observational study was conducted in the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University from IRB clearance to 18 months. The patients who fulfill the selection criteria were enrolled in this study. Written informed consent was taken from the patients and/or the legal guardian/ responsible family members after completely explaining to them the procedure and the purpose of the study. Patient’s data was collected in questionnaire/data collection sheet. The privacy of the patient was strictly maintained and the patient’s information will not be disclosed to any source. The study data will only be used for the purpose of this scientific study. This study was not causing any additional harm to the patients. All the patients were evaluated by a standard conventional contrast-enhanced study with perfusion-weighted image on Siemens 3 Tesla MRI. The histopathological grading of the tumor was done as per the WHO classification of 2007. Then correlation was done between PWI finding and WHO histopathological grading.Results: Measurement of relative cerebral blood volume in glioma patients was done in PW-MRI preoperatively. Out of the 35 tumors evaluated, 17 were found as low rCBV and 18 as high. Histopathological examination of glioma was done postoperatively. Among 35 tumors, 19 are low grade gliomas and 16 are high grade gliomas. For the correlation between relative cerebral blood volume in preoperative PW MRI and histopathological grading of glioma, Spearman’s Rank Correlation Coefficient Test was done. We found a significant positive coefficient value of r = 0.572 with a significant p-value of p =